Antimalaria test of artemisia spp. on Plasmodium falciparum - ., Aryanti; Ermayanti, Tri Muji; Priadi, Kartika Ika; Dewi, Rita Martaleta (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
The testing of inhibiton of Plasmodium falciparum by Artemisia annua, A.cina and A.vulgaris isolate and artemisinin content each of plants was conducted. Artemisia leaves extracted from n-hexane and then separated by column chromatography with n-hexane/ethylacetate as eluent. The column result tested to P.falciparum protozoa. The concentrations of agent were 100, 10, 1 and 0,1 Î¼g/mL using sulphadoxin pyrimetamin as a control positive. Then 50 Î¼l of cell suspension added to agent and incubated at 37oC for 30 hours and the number of live skizon calculated from 200 parasite asexual. The result showed that the increasing of agent concentration was increasing of parasite death. Percent of death parasite by agent of 100 Î¼g/mL similar with positive control at the concentration of 300 Î¼g/mL and the death by A.annua was 83.77%, A.cina 78.57 and A.vulgaris was 84.90% meanwhile positive control was 88.09%. The highest of artemisinin content found in A.annua was 4.99.Key words : anti-malaria, Plasmodium falciparum, Artemisia spp.